Kualitas Fisik dan Mikroba Daging Sapi yang Ditambah Jahe (Zingiber officinale Roscoe) pada Konsentrasi dan Lama Penyimpanan yang Berbeda - Komariah .; I I Arief; Y Wiguna (Faculty of Animal Science, Bogor Agricultural University, 2004)
The objective of this research was to determine the effect of ginger addition in pasta form with different concentration and time of storages on meat tenderness, total microbe, and pH value. The semimembranosus of 2 to 3 years old Brahman Cross muscle from Bogor slaughter house was used for this research. This research was executed at Laboratory of Large Ruminant, Faculty of Animal Science, Bogor Agricultural University. This research used a completely randomized design with factorial pattern 3 x 4 with 3 replications. First factor was concentration of ginger addition consist of 0, 6, and 8% of meat weight and the second factor was time of storage, consisted 0, 3, 6, and 9 days. The result showed that there was no significant difference of ginger concentration on pH value, in contrast there was a significant difference (P < 0.01) of storage time and interaction between factors. The decreasing pH value influenced tenderness and total microbes. Time of storage and interaction between factors showed a significant effect (P < 0.05) on meat tenderness. Interaction occurred on 6 days of meat storage with shear value 4.43 kg/cm3. The highest tenderness value was obtained on 9 days of meat storage for ginger concentration of, 6% and 8%, i.e. 4.02 kg/cm3 and 3.76 kg/ cm3 respectively. Both factors and their interaction showed a significant difference (P < 0.01) on total microbes. The decrease of total microbes occurred on treated samples but in control total microbe increased until 9 days of meat storage. Six percent ginger addition decreased total microbes until 9 days of meat storage that was 1.5 x 106 cfu/g. In 9 days of meat storage the result showed that 6% and 8% ginger addition had total microbes 3.3 x 107 cfu/g and 2.1 x 107 cfu/g respectively. Antimicrobial activity increased as ginger concentration addition increased. Key words: ginger (Zingiber officinale Roscoe), antimicrobial, proteolityc enzyme, total microbes, tenderness